Omics Tools: Approaches for Microbiomes Analysis to Enhance Bioenergy Production - Verma S.; Pandey A.K. (My University, 2025)
Exponentially increasing energy demand and decreasing fossil fuel resources signal alarming conditions in the coming future. Need of renewable, sustainable and eco-friendly energy sources thus becomes obligatory. Biological energy sources and means of production show high potential to meet the scarcity. Biofuels like bioalcohols, biodiesel and biogas are efficiently replacing and supplementing fossil fuel energy. Microorganisms play vital role in biofuel production by catabolizing biomass through in-built pathways or itself can be used as energy source. Till date, complex microbiomes are prevalent for large scale production, resulting in biomass consumption even by less efficient or inhibitory microbes, hence decreasing process efficiency and energy yield. Omics tools comprising transcriptomics, genomics, proteomics and metabolomics have provided ultimate techniques for microbial strain development or improvement to deal such limitations. Henceforth, this chapter focuses on conventional as well as improved microbial systems developed by contribution of omics tools, to meet the current global energy demand. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2020.